HUBUNGAN VENTILASI DENGAN KEJADIAN PENYAKIT ISPA PADA SANTRI DI PONDOK PESANTREN AMANATUL UMMAH SURABAYA - Istifaiyah, Amanatul; Adriansyah, Agus Aan; Handayani, Dwi (Jurnal Ilmu Kesehatan Masyarakat, 2019)
The incidence of Acute Respiratory Infections (ISPA) at the Amanatul Ummah Surabaya Islamic Boarding School is the biggest disease experienced by santri. This study aims to analyze the relationship between ventilation with the incidence of ISPA in students at the Amanatul Ummah Surabaya Islamic Boarding School. Cross sectional and Stratified Random Sampling consist of of 91 male and 116 female students were used in this study.data was obtained through extensive ventilation field observations. Secondary data was obtained from the medical record books of the students to obtain information on the history of the incidence of ISPA experienced by respondents over the past 1 year. The data analysis by chi-square test (α=0.05). The results showed that most (73.9%) respondents had ventilation conditions that did not meet the requirements and most (54.1%) sufferred from ISPA. The results showed a significant correlation between the ventilation condition and the incidence of ISPA (p=0.001). The more ventilation does not meet the requirements, the more likely the respondents were to suffer from ISPA. It was recommended that the islamic boarding schools evaluate the construction of the islamic boarding schools, especially related to the ventilation hole area of the students rooms to fit the applicable health requirements.